Nonlinear Determination Method for Self-Heating Initiative Temperature of Sulfide Ores - Huimin Jin; Wei Pan; Xue Shen; Shuangyi Cheng (Complexity)
The purpose of this article is to explore a new method to determine the self-heating initiative temperature of sulfide ores for preventing spontaneous combustion of sulfide ores. Two typical ore samples with self-heating characteristics are studied by wavelet transform, recursive graph analysis, Hurst index extraction, and approximate entropy detection. On this basis, self-heating initiative temperature of sulfide ores was measured. The results indicate that the Hurst index of both ore samples in the experiment is greater than 0.5; moreover, the Hurst index in the later period of the experiment is greater than that of the earlier period. The self-heating of sulfide ores is an unsteady process with positive persistence and obvious mutation, so the possibility of self-heating of sulfide ores can be determined according to the change characteristics of Hurst index. The mutation times of the two samples are 864 min and 819 min, respectively, reference values of self-heating initiative temperature are 219.4°C and 232.3°C, and the average relative error is only 1.49%, which are in good agreement with the measured values, and therefore, it provides basis for safety production of high-sulfur ore mine.